Rahasia Belajar Ilmu Barokah: Kunci Menuju Kesuksesan di Dunia Pendidikan Menurut Hadratus Syaikh KH Hasyim Asy’ari - Setiawati, Viola Septi Ryan; Sopingi, Imam; Hidayati, Athi’ (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Based on the thoughts of Hadratus Shaykh KH Hasyim Asy'ari, the concept of “The Secret of Learning Barakah Knowledge” is discussed in this article as a key to success in education. Blessed knowledge is understood in Islamic education as knowledge that is academically and spiritually beneficial. He emphasized the importance of integrating science and morals through a holistic approach. This study investigates Hadratus Shaykh KH Hasyim Asy'ari's learning approach, which prioritizes moral and ethical values in every step of education. Data were collected using qualitative methods from various sources, including his writings. The results of this study show that the application of barokah science not only improves the quality of education but also shapes the character of students better. It is hoped that this article will provide new insights for educators and policy makers on how to create a more efficient and sustainable education system that is in accordance with spiritual and moral principles.